ANALISA EFISIENSI EXERGI BOILER WANSON III PADA UNIT KILANG DI PUSAT PENDIDIKAN DAN PELATIHAN MINYAK DAN GAS BUMI ( PUSDIKLAT MIGAS ) CEPU - MSK. Tony Suryo Utomo; Eko Siswanto (JURNAL TEKNIK MESIN, 2015)
This paper discusses the analysis of efficiency exergy of boiler Wanson on refinery unit at PUSDIKLAT MIGAS Cepu is order to identify the actual energy used or the quality results of the actual energy consumption and actual energy loss as a result from irreversible process. Boiler is the biggest source of exergy destruction in a Steam Power Plant’s System and plant systems, hence there is a big opportunity to increase the efficiency in performance. Therefore the bigger efficiency in boiler’s performance, the lower production cost for fuel consumption in industry. Boilers are analyzed using fuel Residue (MFO) on assuming constant environment temperature and pressure of 25oC and 1 bar within twenty-four hours. The result are the average efficiency exergy is 58.13% and the average energy efficiency is 79.60%. Based on the results of the research that the total rate of destruction exergy in the boiler is 34.833 MW or 38.92% of the incoming exergy of 89.501 MW. The rate of destruction combustor accounted for 24.60%, while the rate of destruction of the heat exchanger provides the largest contribution of 14.32%. The total exergy efficiency, total energy efficiency and total destruction rate are influenced by mass flow rate and the temperature of steam. Exergy efficiency and the rate of exergy destruction in  combustor are influenced by fuel temperature, combustion air temperature, excess air, mixing fuel with air and insulation system in the combustor, while the value of the efficiency and the rate of exergy destruction of heat exchanger affected by mass flow rate of steam, flue gas temperature, cleanliness tubes, insulation and the amount of feedwater system wasted in the blowdown system.